Hope health optimizing physical education : for senior high school 2 - Jean Marie D. Cando (Malabon City : Mutya Publishing House, Inc., 2017)
"The entire book presents activities both written and practical which measure students understanding and learning of fitness, health and sports. All topic aim to inculcate in the minds of the learners as well as the people around them the value of regular activity participation for better fitness level now and in the future."
Includes references.
English text.